2022
DOI: 10.3390/atmos13020182
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin Wave and Its Impact on the Venus Atmosphere Tested by Observing System Simulation Experiment

Abstract: At the cloud top of the Venus atmosphere, equatorial Kelvin waves have been observed and are considered to play an important role in the super-rotation. We were able to reproduce the wave in a general circulation model (GCM) by conducting an observing system simulation experiment (OSSE) with the help of a data assimilation system. The synthetic horizontal winds of the Kelvin wave produced by the linear wave propagating model are assimilated at the cloud top (~70 km) in realistic conditions, assuming they are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In this study, we mainly focused on the thermal tide in the analysis for just one period. In the previous data assimilation test studies, it has been reported that the cold collar 49 and planetary-scale Kelvin waves 50 , 51 could be reproduced with sufficiently frequent observations. We are now planning to produce analyses with a number of observation periods, with which such kind of short period disturbances can be reproduced and investigated widely in the Venus research community.…”
Section: Resultsmentioning
confidence: 91%
“…In this study, we mainly focused on the thermal tide in the analysis for just one period. In the previous data assimilation test studies, it has been reported that the cold collar 49 and planetary-scale Kelvin waves 50 , 51 could be reproduced with sufficiently frequent observations. We are now planning to produce analyses with a number of observation periods, with which such kind of short period disturbances can be reproduced and investigated widely in the Venus research community.…”
Section: Resultsmentioning
confidence: 91%